Menarik Perhatian Pelanggan dengan Live TikTok - Aghnia Fakhirah Fauziyah; Indri Rachmawati (UNISBA Press, 2024)
Abstract. Tiktok Live is widely used by entrepreneurs in promotions and sales. TikTok Live can influence prospective customers to buy products that are sold. With the presence of live TikTok, customers can easily find information about the products they are selling. The aim of this research is to find out how TikTok live with customer loyalty. This research uses a quantitative approach with correlational study methods. This research theory uses the AISAS theory (Attention, Interest, Search, Action, Share). The population in this study is TikTok @Screamous_store account followers of 1,748,000 as of December 6, 2023, with samples taken as many as 100 samples based on incidental sampling techniques.This research uses data collection techniques by distributing questionnaires (angket). The results of this research are that H0 is rejected and H1 is accepted, which means there is a strong relationship between live TikTok @screamous_store and customer loyalty. The results of this research also show that the existence of live TikTok can help Screamous maintain customer loyalty. Abstrak. Live TikTok banyak digunakan para pelaku usaha dalam melakukan promosi dan penjualan. Live TikTok dapat memengaruhi calon pelanggan untuk membeli produk yang dijual. Dengan adanya live TikTok, pelanggan dapat dengan mudah mencari informasi tentang produk yang dijual. Tujuan dari penelitian ini yaitu untuk mengetahui hubugan live TikTok dengan loyalitas pelanggan. Penelitian ini menggunakan pendekatan kuantitatif dengan metode studi korelasional. Teori penelitian ini menggunakan teori AISAS (Attention , Interest , Search, Action, Share). Populasi dalam penelitian ini adalah followers akun TikTok @Screamous_store sebanyak 1.748.000 per tanggal 6 Desember 2023 dengan sampel yang diambil sebanyak 100 sampel berdasarkan pada teknik sampling insidental. Penelitian ini menggunakan teknik pengumpulan data dengan menyebarkan kuesioner (angket). Hasil dari penelitian ini adalah H0 ditolak dan H1 diterima yang artinya terdapat hubungan kuat antara live TikTok @screamous_store dengan loyalitas pelanggan. Hasil penelitian ini juga menunjukkan bahwa adanya live TikTok dapat membantu Screamous dalam mempertahankan loyalitas pelanggan.